2002
DOI: 10.1128/iai.70.2.878-888.2002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Biofilms Formed byCandidaalbicansandCandidaparapsilosison Bioprosthetic Surfaces

Abstract: Little is known about fungal biofilms, which may cause infection and antibiotic resistance. In this study, biofilm formation by different Candida species, particularly Candida albicans and C. parapsilosis, was evaluated by using a clinically relevant model of Candida biofilm on medical devices. Candida biofilms were allowed to form on silicone elastomer and were quantified by tetrazolium (XTT) and dry weight (DW) assays. Formed biofilm was visualized by using fluorescence microscopy and confocal scanning laser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
356
2
35

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 455 publications
(437 citation statements)
references
References 52 publications
27
356
2
35
Order By: Relevance
“…Colorimetric assays are valuable for quantifying the viabilities of eukaryotic cells, and it has been suggested the XTT assay is useful to study fungal biofilm formation and drug resistance (Chandra et al ., 2001; Kuhn et al ., 2002). Findings from our XTT assay showed that metabolic activity of biofilm and planktonic C. albicans cells was not affected after 7‐benzyloxyindole treatment at 0.02 and 0.05 mM (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Colorimetric assays are valuable for quantifying the viabilities of eukaryotic cells, and it has been suggested the XTT assay is useful to study fungal biofilm formation and drug resistance (Chandra et al ., 2001; Kuhn et al ., 2002). Findings from our XTT assay showed that metabolic activity of biofilm and planktonic C. albicans cells was not affected after 7‐benzyloxyindole treatment at 0.02 and 0.05 mM (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Altman (1976) reported mitochondrial succinoxidase, cytochrome P450 and flavoprotein oxidases are primarily responsible for the conversion of XTT to coloured formazan, which is important in fungal research because XTT conversion provides a measure of metabolic activity, which is related to fungal wall biosynthesis. (Kuhn et al ., 2002). This findings imply that 7‐benzyloxyindole at concentrations of >0.1 mM reduced metabolic activity due to low levels of C. albicans cells in biofilms (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Ramage et al (2002) found Defg1 sessile cells to be equally resistant to AmB compared to the WT. Such inter-study variations highlight the differences in susceptibilities of Candida biofilms, which can be strongly influenced by different setups, including the type of device, composition and pH of the medium (Kucharíková et al, 2011) and the quantification/susceptibility methods used (Kuhn et al, 2002b).…”
Section: Discussionmentioning
confidence: 99%
“…differ in their capacity to form biofilms [23]. Mature Candida biofilms exhibit a complex three-dimensional structure and display extensive spatial heterogeneity [21,23,24]. The overall architecture of the biofilm may vary depending on the substrate on which it is formed and its growth conditions [25].…”
Section: Page 9 Of 42mentioning
confidence: 99%
“…Different strains of C. albicans and different Candida spp. differ in their capacity to form biofilms [23]. Mature Candida biofilms exhibit a complex three-dimensional structure and display extensive spatial heterogeneity [21,23,24].…”
Section: Page 9 Of 42mentioning
confidence: 99%